Foreign body granuloma mimicking malignancy: a diagnostic challenge post-caesarean section - Khan, Farheen; Shirazi, Alina; Siddiqa, Munazza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Foreign body granulomas arising from haemostatic agents such as oxidized regenerated cellulose (Surgicel) are rare but can closely mimic malignancy on imaging, resulting in unnecessary investigations, delays in treatment, and significant patient anxiety. Authors report the case of a 33-year-old para 1 woman who presented with lower abdominal pain and urinary symptoms eight months after elective caesarean section in which Surgicel was used. Imaging studies suggested a malignant mass involving the cervix, bladder, and vagina, with suspicious lymphadenopathy. Cystoscopy and drainage procedures were inconclusive. Exploratory laparoscopy revealed a 7×5 cm organized mass containing gelatinous material in the uterovesical pouch. Histopathology confirmed a foreign body granuloma with giant cell reaction to suture material. The patient recovered uneventfully following excision. Postoperative suture granulomas should be considered in the differential diagnosis of pelvic masses following caesarean section or other gynecological surgeries where haemostatic agents have been used. Early recognition can prevent unwarranted investigations and improve patient outcomes.